Optimalisasi Pengelolaan Zakat sebagai Instrumen Dakwah dalam Pemberdayaan Ekonomi Umat - Nur Sai’dah, Sinta; Aziz, Rohmanur; Aziz, Ali (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2015)
Zakat is able to form a process of social care in overcoming poverty to help each other to relatives in need. The research was conducted to find out the process of planning activities, forms of organizing, coordinating efforts and monitoring systems at LAZNAS Orphanage Indonesia in improving the welfare of the people. The research method used is descriptive method with a qualitative approach. Data collection techniques are observation, interviews, and documentation. Based on the results of the research, it shows that LAZNAS Orphanage Indonesia has done well based on the management function. In planning activities through several stages such as a clear vision and mission, strategies through the survey and assessment stages as well as donor resources. Organizing is done by dividing the duties and responsibilities of each field, program details and division of labor. In addition, coordination has created a work agreement with alignment in directing leaders and resources. The results of supervision follow performance standards and facilities through standard service facilities and the behavior of administrators based on program activities.